PEMODELAN BANGKITAN PERGERAKAN PADA TATA GUNA LAHAN SEKOLAH MENENGAH PERTAMA SWASTA DI KOTA PALEMBANG - virta dwi nugraha (Jurnal Teknik Sipil dan Lingkungan, 2014)
This research was done in 7 private senior high schools in Palembang. The purpose is to know trip generation factors and to make the model of picker and taker trip generation vehicles (private car, motorcycle and public transport). Last research did the same thing to get the model which used double linear regression like mine. There are primary and secondary data where primary is picker and taker vehicles data then secondary is student amount (XI), teacher amount (X2), school wide (X3), class amount (X4), class capacity (X5), park area wide (X6), class wide (X7), facility amount (X8), teacher’s vehicle amount (X9). All of them is tabulated to free and bound variable, then analyzed by SPSS-17 program. The result shows the best model to describe Trip Attraction to SMP Swasta Palembang for student picker and taker vehicles (private car, motorcycle and public transport) are Y = 140,950 + 0,685X1 -2,857X4 - 1,395X8 with R2 0,872. But the best model to describe Trip Production for student picker and taker vehicles (private car, motorcycle and public transport) are Y =204,366 + 0,398X1 + 1,848X4 - 2,446X8 with R2 0,659. Keywords: trip generation model, trip attraction, trip production, private high school